Bridging the Proficiency Gap: Translanguaging as an Inclusive Pedagogy in Teaching Narrative Texts - Syawal Syawal; Hasman Hasman; Nurul Isnaini; Yuziana Yasin (Universitas Sulawesi Barat, 2026)
This study investigated the effectiveness of translanguaging strategies in improving students' reading comprehension at MTs DDI Amparita. Low literacy levels and monolingual bias in English instruction have contributed to students' difficulties in comprehending narrative texts. This research aimed to determine whether translanguaging could serve as a better pedagogical alternative to code-switching. Employing a quasi-experimental design, the study involved 38 eighth-grade students, divided into an experimental group taught through translanguaging and a control group taught through code-switching. Data were collected using a reading comprehension test administered before and after the treatment. The results revealed that the experimental group achieved a significantly higher mean score (86.78) compared to the control group (61.68). The t-test analysis confirmed a significant difference (t = 7.349), exceeding the t-table value of 2.101. Furthermore, the analysis showed a smaller standard deviation in the experimental group, indicating a more even distribution of learning outcomes. It is concluded that translanguaging not only improves comprehension but also promotes inclusivity by reducing the proficiency gap among students. Teachers are suggested to integrate translanguaging systematically to foster a more engaging and equitable learning environment.